Journal of Agricultural & Food Industrial Organization (De Gruyter, 2003)
The Journal of Agricultural & Food Industrial Organization (JAFIO) is a unique forum for empirical and theoretical research in industrial organization with a special focus on agricultural and food industries worldwide. JAFIO is the only international journal devoted solely to theoretical and empirical industrial organization as applied to agricultural and food systems which link input suppliers, farmers, processors, and retailers.